Mixotrophy in Land Plants: Why To Stay Green? - Tĕšitel, Jakub; Těšitelová, Tamara; Minasiewicz, Julita; Selosse, Marc-André (Trends in plant science, 2018)
Mixotrophic plants combine photosynthesis and heterotrophic nutrition. Recent research suggests mechanisms explaining why mixotrophy is so common in terrestrial ecosystems. First, mixotrophy overcomes nutrient limitation and/or seedling establishment constraints. Second, although genetic drift may push mixotrophs to full heterotrophy, the role of photosynthesis in reproduction stabilizes mixotrophy.
Keywords: biologická evoluce; Reproduction; ekosystém; Genetic Drift; heterotrophy; Heterotrophic Processes; Biological Evolution; genetický drift; plant parasitism; heterotrofní procesy; fotosyntéza; mycoheterotrophy; mycorrhizae; Photosynthesis; vyšší rostliny; Embryophyta; rozmnožování; Ecosystem; evolutionary metastability